PENGARUH GAYA HIDUP SEHAT TERHADAP PSYCHOLOGICAL WELL-BEING DAN DAMPAKNYA PADA AUDITOR KAP (Studi Empiris pada Auditor Kantor Akuntan Publik di Jawa Tengah Dan DIY) - Angelina Ave Gratia; Aditya Septiani (Diponegoro Journal of Accounting, 2014)
Some of the career conditions in Public Accounting Firm (KAP) contribute to the difficult situation faced by the auditor therefore auditor facing irregular stress levels. Past research has shown the negative impact of role stress experienced by auditor, especially during the busy season. At the individual level, stressful work situation cause problems and sometimes makes a lot of capable auditor resign from KAP. At the organizational level, the firm will have more frequent voluntary turnover disfungsionality. This study examines the effect of role stress (role ambiguity, role conflict, and role overload) experienced by auditor to job outcomes (job satisfaction, job performance, and turnover intentions) and the role of healthy lifestyle as a coping mechanism the role of stress on the KAP.The samples used in this study were taken by  using a convenience sampling method. The population was all auditor who worked at the firm in Central Java and Yogyakarta. The method used in data collection is the primary method of data collection, using questionnaires filled out directly by auditor as respondents of the study. A technique of analysis in this study is Structural Equation Model (SEM) by statistical programs SmartPLS.The results show that a healthy lifestyle that practiced by auditors can be an alternative solution as a mechanism to mitigate the negative effects of role stressors. Healthy lifestyle mediated by a vitality and increase in psychological well-being, will reduce the negative effects of role stress mediated by job burnout and psychological well-being, resulting in a positive association with job satisfaction and job performance, but has not yet proved capable of reducing the high turnover intentions in Public Accounting Firm .